A Review of Assured Data Deletion Mechanism in Cloud Computing - Ahmad, Sultan; Mohammad Mazhar Afza, Dr. (International Journal of Engineering and Technology, 2018)
As Cloud Computing has become a new way to store information remotely. It makes possible for many companies to become paperless. IT people and companies can outsource their huge data by using this emerging technology. The major important characteristics of cloud computing are on-demand self-service, broad network access, resource pooling, rapid elasticity and measured services. These cloud computing characteristics are helpful for organizations to become agile. Also there are few serious problems like security, scalability, availability and interoperability which are associated with the above cloud computing characteristics. Providing a secure and efficient access and retrieval of the valuable data is a main concern of cloud computing technologies. It is very important to protect data and credentials of cloud client on the internet. Apart from these security issues of data, the deletion of data on cloud storage is also a very serious issue nowadays.Â  Once a cloud user wants to delete his data, it must be sure that data actually deleted from all cloud storage sources and there should not be remain any copy of data exist at anywhere in cloud storage anyway. In this paper, different existing data deletion and retrieval methods are studied, observed and analyzed. The importance and related challenges to assured data deletion on the cloud storage are explored.Â Â